1989
DOI: 10.1128/jvi.63.9.3954-3960.1989
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus-associated protein kinase: destabilization of the virus capsid and stimulation of the phosphorylation reaction by Zn2+

Abstract: The previously described poliovirus-associated protein kinase activity phosphorylates viral proteins VPO and VP2 as well as exogenous proteins in the presence of Mg2+. In this paper, the effect of Zn2+ on the phosphorylation reaction and the stability of the poliovirus capsid has been studied in detail and compared to that of Mg2+. Phosphorylation patterns of viral and other proteins depend on the divalent cation present. In the presence of Zn2+, phosphorylation of capsid proteins VP2 and VP4 is significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…An effect of protein phosphorylation on the stability of poliovirus capsids and its consequent involvement in viral uncoating was described some years ago (31). More recently, it has been shown that phosphorylation of PVA CP affects its capacity to interact with RNA, suggesting that this modification might contribute to the control of the amount of genomic RNA available for translation, replication, encapsidation, and movement (16).…”
Section: Discussionmentioning
confidence: 99%
“…An effect of protein phosphorylation on the stability of poliovirus capsids and its consequent involvement in viral uncoating was described some years ago (31). More recently, it has been shown that phosphorylation of PVA CP affects its capacity to interact with RNA, suggesting that this modification might contribute to the control of the amount of genomic RNA available for translation, replication, encapsidation, and movement (16).…”
Section: Discussionmentioning
confidence: 99%
“…the regulation of cellular processes, it is not surprising that virus-encoded proteins have adopted this mode of regulation as well. For example, a poliovirus-associated protein kinase has been implicated in the phosphorylation-dependent destabilization of the viral capsid during the uncoating process (30).…”
Section: Kpnl Bglllmentioning
confidence: 99%
“…These results offer interesting parallels with a number of other viruses such as poliovirus, human immunodeficiency virus type 1 (HIV-1), hepatitis B virus, and human respiratory syncytial virus (HRSV) for which the phosphorylation of the viral capsid proteins has been shown to affect infectious entry and capsid stability and disassembly (50)(51)(52)(53). In the case of PVs, it would appear that phosphorylation at a site just downstream of the transmembrane domain of L2 aids capsid disassembly.…”
Section: Discussionmentioning
confidence: 77%